On pickles: biological and sociocultural links between fermented foods and the human gut microbiome - Andrew Flachs; Joseph D. Orkin (BMC, 2021)
Abstract Background The composition of the human microbiome varies considerably in diversity and density across communities as a function of the foods we eat and the places we live. While all foods contain microbes, humans directly shape this microbial ecology through fermentation. Fermented foods are produced from microbial reactions that depend on local environmental conditions, fermentation practices, and the manner in which foods are prepared and consumed. These interactions are of special interest to ethnobiologists because they link investigations of how people shape and know the world around them to local knowledge, food traditions, local flora, and microbial taxa. Methods In this manuscript, we report on data collected at a fermentation revivalist workshop in Tennessee. To ask how fermentation traditions are learned and influence macro and micro ecologies, we conducted interviews with eleven people and participated in a four-day craft fermentation workshop. We also collected 46 fermented food products and 46 stool samples from workshop participants eating those fermented foods. Results We identified ten major themes comprised of 29 sub-themes drawn from 326 marked codes in the transcripts. In combination, this analysis allowed us to summarize key experiences with fermentation, particularly those related to a sense of authenticity, place, health, and the discovery of tactile work. From the 605 amplicon sequence variants (ASVs) shared between food and fecal samples, we identified 25 candidate ASVs that are suspected to have been transmitted from fermented food samples to the gut microbiomes of the workshop participants. Our results indicate that many of the foods prepared and consumed during the workshop were rich sources of probiotic microbes. Conclusions By combining these qualitative social and quantitative microbiological data, we suggest that variation in culturally informed fermentation practices introduces variation in bacterial flora even among very similar foods, and that these food products can influence gut microbial ecology.